2006
DOI: 10.1038/nsmb1150
|View full text |Cite
|
Sign up to set email alerts
|

Structural analysis of kasugamycin inhibition of translation

Abstract: The prokaryotic ribosome is an important target of antibiotic action. We determined the X-ray structure of the aminoglycoside kasugamycin (Ksg) in complex with the Escherichia coli 70S ribosome at 3.5-Å resolution. The structure reveals that the drug binds within the messenger RNA channel of the 30S subunit between the universally conserved G926 and A794 nucleotides in 16S ribosomal RNA, which are sites of Ksg resistance. To our surprise, Ksg resistance mutations do not inhibit binding of the drug to the ribos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
119
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(127 citation statements)
references
References 43 publications
6
119
0
2
Order By: Relevance
“…Unmethylated 30S subunits produced tetragonal crystals in the same space group, P4 1 2 1 2, that are obtained with fully methylated subunits from wild-type T. thermophilus, but crystallized slowly as small needles over a period of 1 yr, rather than in the 2 mo normally required for 30S subunits. Crystallization of unmethylated subunits was completely inhibited by kasugamycin, suggesting that T. thermophilus ksgA 30S subunits retain the ability to bind kasugamycin, as previously observed with an E. coli ksgA mutant (Schuwirth et al 2006).…”
Section: Resultssupporting
confidence: 58%
“…Unmethylated 30S subunits produced tetragonal crystals in the same space group, P4 1 2 1 2, that are obtained with fully methylated subunits from wild-type T. thermophilus, but crystallized slowly as small needles over a period of 1 yr, rather than in the 2 mo normally required for 30S subunits. Crystallization of unmethylated subunits was completely inhibited by kasugamycin, suggesting that T. thermophilus ksgA 30S subunits retain the ability to bind kasugamycin, as previously observed with an E. coli ksgA mutant (Schuwirth et al 2006).…”
Section: Resultssupporting
confidence: 58%
“…Similarly, we found that the steady-state level of lysC mRNA is increased significantly in the presence of the antibiotic kasugamycin (SI Appendix, Fig. S8B), which specifically blocks initiating ribosomes at the RBS (35). However, even in the complete absence of ribosome binding (RBS mutant), a similar lysine-dependent reduction of the mRNA level is still observed (approximately twofold as compared with the wildtype) (Fig.…”
Section: Discussionmentioning
confidence: 73%
“…In particular, the dimethylamine of m 6 2 A1519 is involved in medium and long-range repulsive interactions with the backbone of m 3 U1498 and the 2' O of C1520, while its conformation is mostly determined by the dimethylamine moiety of the adjacent m 6 2 A1518 which, in turn, is fixed by short repulsive interactions with O6 of G1517 and O4 of U793. The additional methyl groups of m 6 2 A1519 interact with A792, which provides part of the binding site for the antibiotic kasugamycin 15 , accounting for the resistance against kasugamycin upon demethylation of m 6 2 A1519 66 . Furthermore, m 6 2 A1518 and m 6 2 A1519 impact initiation 67 possibly via m 3 U1498 whose backbone interacts with m 6 2 A1519, while its modified base contacts the mRNA backbone.…”
Section: Extended Datamentioning
confidence: 99%
“…The P-site codon directly contacts m 4 Cm1402 and m 3 U1498 in 16S rRNA, which in turn are held in place by the bulky dimethylamine groups on m 6 2 A1519 and m 6 2 A1518. The network of long-range interactions provides the basis for the action of the antibiotic kasugamycin, which binds in the P site and requires dimethylation of m 6 2 A1519 for its function 15 . In the A site of the decoding centre, the aminoglycoside class of antibiotics directly binds to a monomethylated residue, m 5 C1407 in 16S rRNA, which is needed for optimum drug activity 16 (Extended Data Fig.…”
mentioning
confidence: 99%